2022
DOI: 10.1002/anie.202207684
|View full text |Cite
|
Sign up to set email alerts
|

Radical Hydro‐Fluorosulfonylation of Unactivated Alkenes and Alkynes

Abstract: Recently, radical fluorosulfonylation is emerging as an appealing approach for the synthesis of sulfonyl fluorides, which are highly in demand in various disciplines, particularly in chemical biology and drug discovery. Here, we report the first establishment of radical hydro‐fluorosulfonylation of alkenes, which is enabled by using 1‐fluorosulfonyl 2‐aryl benzoimidazolium (FABI) as an effective redox‐active radical precursor. This method provides a new and facile approach for the synthesis of aliphatic sulfon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 123 publications
1
34
0
Order By: Relevance
“…While the synthesis of unsaturated ((hetero)­aryl, alkinyl, alkenyl) sulfonyl fluorides has been extensively studied, the synthesis of aliphatic sulfonyl fluorides with high flexibility of substitution pattern remains underdeveloped. , Employing our developed EnT-mediated hydro-fluorosulfonylation conditions (Figure C), we turned toward investigating the alkene scope (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the synthesis of unsaturated ((hetero)­aryl, alkinyl, alkenyl) sulfonyl fluorides has been extensively studied, the synthesis of aliphatic sulfonyl fluorides with high flexibility of substitution pattern remains underdeveloped. , Employing our developed EnT-mediated hydro-fluorosulfonylation conditions (Figure C), we turned toward investigating the alkene scope (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…We further concluded that switching the reactivity mode by introducing a hydrogen atom donor could enable the rapid synthesis of the aliphatic sulfonyl fluorides. Notably, while our studies were underway, Wang and co-workers as well as Song and Liao and co-workers reported the hydro-fluorosulfonylation of alkenes by utilization of benzimidazolium salts as sulfonyl fluoride radical precursors and cyclohexadiene as hydrogen source by photoredox catalysis.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the basis of these results and related mechanistic studies in the literature, , we outline a possible mechanism (Figure C). Under blue LED irradiation, the organic photocatalyst (ODA) can be excited [ E 1/2 (ODA*/ODA •+ ) = −1.76 V vs SCE] and then reduce redox-active radical precursor 2a ( E 1/2 = −1.07 V vs SCE) via a single-electron transfer (SET) process. Consequently, a homolytic fission of the N–S bond in 2a′ delivers the desired FSO 2 radicals.…”
mentioning
confidence: 99%
“…As a continuation of our interest in radical fluorosulfonylation, , herein, we report the development of a radical fluorosulfonylation of alkenes/intramolecular arylation sequence for the synthesis of FSO 2 -functionalzied chromanes (Figure C), based on the fluorosulfonyl radical precursor, FABI, newly developed in our laboratory , with ODA as an organic photoredox catalyst. Notably, both endo and exo cyclization can be adopted to access different structures.…”
mentioning
confidence: 99%